Integrated farming improves livelihood of small farmers - Mubarak, T; Sheikh, F A (Indian Farming, 2015)
Integrated Farming System has many advantages. It introduces a change in the farming techniques for maximum production in the cropping pattern and takes care of optimal utilization of resources. The farm wastes are recycled for productive purposes in the integrated system and also with the farmers’ participatory mode, it helps to motivate and educate the farmers of the area for adopting such models.